The spongillafly genus Sisyra Burmeister, 1839 (Neuroptera: Sisyridae) from Brazil: Distributional, taxonomical and bionomical notes - Assmar, Alice Carvalho; Calor, Adolfo Ricardo (Zootaxa, 2020)
Sisyridae is a small family of aquatic insects, with 73 extant species described worldwide. In Brazil, 17 species of two genera, Climacia McLachlan, 1869 and Sisyra Burmeister, 1839, have been reported. In this paper, the family is recorded from the Caatinga biome (semiarid region), Northeastern Brazil, for the first time, including a record of the genus Sisyra from Ceará State. Additional distributional data are presented for both S. apicalis Banks, 1908 and S. panama Parfin & Gurney, 1956. Sisyra ariasi Penny, 1981 is here synonymized with S. panama, NEW SYNONYMY. Illustrations of the male genitalia of S. minuta Esben-Petersen, 1935, and bionomic notes for S. panama are provided.